Brenneria tiliae sp. nov., isolated from symptomatic Tilia × moltkei and Tilia × europaea trees in the UK. Issue 10 (7th October 2022) - Kile, Helene; Arnold, Dawn; Allainguilaume, Joel; Denman, Sandra; Brady, Carrie
Abstract : Several strains of a previously undescribed bacterial species were isolated from mature Tilia hybrid trees suffering from bleeding cankers at various geographic locations in the UK. The strains were Gram-negative, facultatively anaerobic, and partial sequencing of the gyrB gene revealed that the strains belong to the genus Brenneria with the closest phylogenetic neighbours being Brenneria corticis and Brenneria nigrifluens . Further investigation using a polyphasic approach was undertaken to determine the taxonomic position of the novel species. Phylogenies based on the 16S rRNA gene and multilocus sequence analysis of partial housekeeping gene sequences of gyrB, rpoB, infB and atpD revealed that the strains formed an independent cluster within the genus Brenneria . The phenotypic and chemotaxonomic assays demonstrated that the strains could be differentiated from the closest relatives. Genome analysis of representative strains revealed in silico DNA–DNA hybridization values below the threshold for species delimitation, although the average nucleotide identity values obtained when compared to B. corticis (95.9–96%) were slightly higher than the suggested cut-off value of 95%. However, as all other data suggests that the strains belong to a novel taxon that can be differentiated from the closest relatives, we propose that the strains represent a novel species in the genus Brenneria, Brenneria tiliae sp. nov. (type strain WC1b.1 T =LMG 32575 T =NCPPB 4697 T ).